Optimalisasi pemanfaatan layanan perpustakaan melalui pendidikan pemakai di perpustakaan Pusat UIN Maulana ?Malik Ibrahim Malang - Heni Kurnia Ningsih; Dian Anesti; Tutik Sulistyorini ‎ (IJAL (Indonesian Journal of Academic Librarianship), 2023)
This article discusses the importance of user education in optimizing the use of library services, especially in higher education. The objectives, levels, and evaluation of user education programs are described in detail. The obstacles in integrating this program into the curriculum are also discussed. A case study at the UIN Maulana Malik Ibrahim Central Library shows the positive impact of user education on improving library services, including increasing the number of visitors and book loans. In conclusion, user education is a strategic program to increase user independence in utilizing library resources optimally.